Pengaruh Kombinasi Serat Karbon-Serat Sabut Kelapa Terhadap Kekuatan Impact dan Bending pada Aplikasi Helm Sepeda Motor - Fajar Andi Nugroho; Mohamad Hakam; Widya Emilia Primaningtyas (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
Coconut coir fiber is a fiber derived from coconut shell waste which has economic value, is easy to process and easy to develop for the environmentally friendly composite industry, especially for motorcycle helmets. Carbon fiber is a synthetic fiber made of polyacrylonitrile, a study was conducted to see the response of variations in coconut fiber and carbon fiber layers on the impact and bending strength of composites used for motorcycle helmet applications. The use of synthetic carbon fiber in this composite provides several advantages including high tensile strength, relatively lighter weight, and low thermal expansion so that when combined with natural fibers, in this case coconut fiber, it will increase its structural strength. In this study, the bending strength of 50.765 MPa and impact strength of 0.038 J/mm2 were produced. The two highest values from each of these tests were obtained from the composite composition using 3 layers of carbon fiber and 2 layers of coconut fiber.